Biochemical determinants of the severity of Haemolysis in patients with G6PD deficiency - ZEENA ABDUL ILAH; SAHAR ABDUL WAHAB AL-SHABAN (International Journal of Pharma and Bio Sciences, 2018)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency represents a major health problem for Iraqis, especially during the fava bean harvesting season. This study aimed to assess the clinical and biochemical characteristics as predictors of severe haemolysis among these patients. A total of 98 patients with G6PD deficiency were recruited from the Emergency Department of Al-Karama Teaching Hospital. Patients were classified into either non-severe or severe haemolysis groups based on their haemoglobin level at the time of admission. Of the 98 cases, 48 (48.98%) were diagnosed as severe haemolysis. Logistic regression revealed that younger age (expand AOR AOR: 0.77, p < 0.05), living in rural region (AOR: 3.14, p < 0.01), ingesting fresh fava beans (AOR: 1.99, p < 0.01), history of frequent haemolysis (AOR: 2.73, p < 0.01), jaundice (AOR: 1.55, p < 0.05), lethargy (AOR: 1.69, p < 0.05), high total serum bilirubin (AOR: 1.34, p < 0.05), high lactate dehydrogenase (AOR: 1.42, p < 0.05), high reticulocyte count (AOR: 2.31, p < 0.01), and deep dark coloured urine at admission (AOR: 3.17, p < 0.001) were predictors of severe haemolysis. Severe haemolysis among G6PD patients can be predicted by several clinical and biochemical factors.